Meat quality and intramuscular fatty acid composition of Catria Horse. (2nd December 2016) - Trombetta, Maria Federica; Nocelli, Francesco; Pasquini, Marina
Abstract: In order to extend scientific knowledge on autochthonous Italian equine meat, the physical–chemical parameters of Catria Horse Longissimus thoracis (LT) muscle and its nutritional characteristics have been investigated. Ten steaks of Catria foal raised at pasture and fattened indoors for 2 months were dissected, and LT muscle was analyzed for chemical composition, total iron, drip loss, colorimetric characteristics, intramuscular fat, fatty acid profile and nutritional indexes. Steak dissection showed that LT muscle accounted for 36.78% and fat accounted for 9.19% of weight of steak. Regarding chemical composition, protein and fat content was 20.31% and 2.83%, respectively. Total iron content (1.95 mg/100 g) was lower than data reported in the literature. Color parameters showed a luminous and intense red hue muscle. The sum of unsaturated fatty acid composition (50.3%) was higher than the sum of saturated fatty acids (46.64 %). The fatty acid profile and nutritional values of Catria Horse meat could be modified adopting extensive rearing systems and grazing. The data suggests that further investigation on the composition of Catria Horse meat should be carried out to valorize this autochthonous breed, reared in sustainable livestock systems, and its meat in local short‐chain systems.